Indole Alkaloids and Phenolic Amides from the Rhizomes of Cimicifuga heracleifolia and Their In Vitro Soluble Epoxide Hydrolase (sEH) Inhibitory Activity - Yanwen Sun; Chunyu Fan; Liyi Chen; Xueting Cui; Kouharu Otsuki; Mi Zhang; Feng Qiu; Liqin Ding; Wei Li (Plants)
Cimicifuga heracleifolia is a perennial herb that belongs to the Ranunculaceae family. Its dried rhizomes are a source of Cimicifugae Rhizoma, a traditional Chinese medicine used for detoxification, the treatment of febrile diseases, and the prevention of pathogenic invasion. In the present study, a phytochemical investigation of the rhizomes of C. heracleifolia resulted in the isolation of three indole alkaloids (1–3) and seven phenolic amides (4–10), including three new compounds, 6-methoxy-3-(3-methyl-1-oxo-2-butenyl) 1H indole (1), (3R)-1-(β-d-glucopyranosyl)-3-hydroxy-3-(3-methylbutyl)-2-oxindole (3), and N-acetyldopamine-3-O-β-d-allopyranoside (4). Their structures were elucidated using extensive physicochemical and spectroscopic analyses. All the isolated compounds were evaluated for their inhibitory activity against soluble epoxide hydrolase (sEH). The results showed that cimicifugamide A (6) exhibited the most potent inhibitory activity, with an IC₅₀ value of 8.74 μM, followed by cimicifugamide (7), demethoxycimicifugamide (8), and N-trans-feruloyl tyramine (10), with IC50 values ranging from 15.63 to 20.58 μM. Kinetic analysis revealed that compound 6 inhibited sEH through a non-competitive mechanism.